Overview of Family Economic Status and Environmental Sanitation of Stunting Toddler Homes - Endrastya Pramahdyta; Yulia Susanti; Dona Yanuar Agus Santoso; Muhammad Khabib Burhanuddin Iqomh (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Stunting is a malnutrition problem in children characterized by a short body with a size of <-2 elementary school, this greatly affects the quality of life of children in the future. The stunting prevalence of Kendal district was recorded at 4,324 people under five. Some of the factors that cause stunting include parental caregiver practices, family income, education level, employment, number of family members, environmental sanitation, and access to health services. The purpose of this study is to determine the picture of family economic status and sanitary conditions of the home environment of stunting toddlers. This study is a descriptive survey study with a cross sectional approach with a population of 680 people, a sample of 251 people. Implementation of research in five areas of Puskesmas Kendal Regency stunting locus area. The results of this study found that the average age of parents of stunting toddlers was 33 years, mothers with high school education 43.8%, fathers with junior high school education 45.8%, male toddlers 52.6%, classification of stunting toddlers in the very short category 52.6%, the majority of family economic status under UMK Kendal 68.1%, and sanitary conditions of the family home environment in the medium category 44.6% and less 14.7%. This study describes the economic status of stunting toddler families in the low category under Kendal MSEs and the sanitary conditions of the home environment are lacking. Families are expected to strive to improve the family economy and sanitation facilities, a healthy home environment, and behave clean and healthy.